Yoga in Arterial Hypertension: A Three-Armed, Randomized Controlled Trial. - Cramer, Holger; Sellin, Charlotte; Schumann, Dania; Dobos, Gustav (Deutsches Ärzteblatt International, 2018)
Background: Yoga seems to exert its effect against arterial hypertension mainly through the associated breathing and meditation techniques, and less so through yoga postures. The goal of this trial was to compare the blood pressure-lowering effect of yoga interventions with and without yoga postures in patients with arterial hypertension. Methods: 75 patients taking medications for arterial hypertension (72% women, mean age 58.7 ± 9.5 years) were randomized into three groups: a yoga intervention group with yoga postures (25 patients, of whom 5 dropped out of the trial before its end), a yoga intervention group without yoga postures (25 patients, 3 dropouts), and a wait list control group (25 patients, one dropout). The interventions consisted of 90 minutes of yoga practice per week for twelve weeks. The data collectors, who were blinded to the intervention received, assessed the primary outcome measures "systolic 24-hour blood pressure" and "diastolic 24-hour blood pressure" before and after the intervention. In this report, we also present the findings on secondary outcome measures, including follow-up data. Results: After the intervention, the systolic 24-hour blood pressure in the yoga intervention group without yoga postures was significantly lower than in the control group (group difference [Δ]= -3.8 mmHg; [95% confidence interval (CI): (-0.3; -7.4) p = 0.035]); it was also significantly lower than in the yoga intervention group with yoga postures (Δ = -3.2 mmHg; 95% CI: [-6.3; -0.8]; p = 0.045). Diastolic blood pressures did not differ significantly across groups. No serious adverse events were encountered in the course of the trial. Conclusion: In accordance with the findings of earlier studies, we found that only yoga without yoga postures induced a short-term lowering of ambulatory systolic blood pressure. Yoga is safe and effective in patients taking medications for arterial hypertension and thus can be recommended as an additional treatment option for persons in this category.